Railway development and the impact to Malaysian economy - Abd Aziz, Sahrir; Kassim, Rozilah; Mohd Masirin, Mohd Idrus (JARDCS, 2018)
The development of railway system in Malaysia is no longer seen to fit a needs of land transportation system only. The development currently is more to be a method to improve the existing service, making public transportation system more widespread and effective. It is also an alternative method to solving traffic congestion in the city. In recent decade, development of rail system in Malaysia is not only focused to the city center, but also the provision and construction of several routes connecting the Kuala Lumpur city center to the surrounding areas which allow residents of outside the city working in Kuala Lumpur without having to live in the city. In addition, a construction of two-way rail system to replace an existing one-way rail made aggressively across the country as an effort to make the rail transportation system more efficient and faster for services. Therefore, the system will becoming a preferred mode of transport in the near future compared to the road transport system. In the recent years, the Government is giving more attention to the rail transportation system and has approved another two new projects to build a new route from Klang Valley to Tumpat, Kelantan and also the construction of the Kuala Lumpur – Singapore high speed train network. The transport sector is currently an important infrastructure in enhancing the economic development of Malaysia at the global level. Advanced pullback of a country can be seen and measured by its public transport system. These two new projects, upgrading the existing rail routes and added by the rapid development of rail transportation system in Klang Valley are believed to give an impact to the economy of the country as a whole.